Delayed brain injury post carbon monoxide poisoning - Jahinover Mazo, MD; Eyas Mukhtar, MD, MBA; Yuliya Mazo; Abhiram Nagaraj, MD; Michael T. Mantello, MD (Radiology Case Reports, 2020)
A 66-year-old male was found unresponsive and diagnosed with acute carbon monoxide poisoning, with pathognomonic findings on radiological imaging. During his first day's the patient underwent acute neurological deterioration; however, this was followed 2 weeks later with a subsequent improvement to near baseline. The improvement back to baseline was short-lived, and the patient quickly worsened and underwent neurological decompensation. These findings were consistent with delayed post hypoxic leukoencephalopathy, serious sequelae of carbon monoxide poisoning. This case report shows the importance of recognition of carbon monoxide toxicity and aims to improve accurate diagnosis of the sequelae that may follow using computed tomography and magnetic resonance imaging sequences, magnetic resonance spectroscopy in order to prevent or ameliorate further neurological decline.